Citra Jurnalis Di Kalangan Warga Pedamaran 6 Tentang Idealisme Jurnalistik Dan Pragmatisme Politik - Despriadi; Eni Murdiati; Ahmad Harun Yahya (CV. ITTC INDONESIA, 2023)
Some parties still view political reporting as the responsibility of journalists. Depending on the different points of view taken, media A and media B can sometimes report in very different ways from each other. Public trust in the media is being eroded by both politicians and media figures. This will be a problem if the news is too politicized or demands political justification from the public. The aim of this research is to describe how society views journalists from the perspective of political pragmatism and journalistic idealism. Naturalistic descriptive research methods were used in this research to conduct qualitative research. The research subjects were three (three) residents of Pedamaran 6 Village and officials who had or are still carrying out entrepreneurial ventures or activities related to the village. In-depth interviews and documentation were used as data collection methods. The interactive model developed by Miles and Huberman is used in data analysis techniques, including data collection, data reduction, data presentation, and drawing conclusions. The findings of this study show that when pragmatic politics runs rampant in the media, journalists' reputations will suffer. The interference of media owners basically prevents journalists from upholding their ideals and complying with journalistic codes of ethics. The inability of journalists to uphold idealistic commitments in upholding a code of ethics is partly caused by concern for their welfare and ability to meet their needs.